2012
DOI: 10.1208/s12249-012-9848-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Sustained-Release Matrix Tablets Based on Metoprolol and an Acrylic Carrier Using Injection Moulding

Abstract: Abstract. Sustained-release matrix tablets based on Eudragit RL and RS were manufactured by injection moulding. The influence of process temperature; matrix composition; drug load, plasticizer level; and salt form of metoprolol: tartrate (MPT), fumarate (MPF) and succinate (MPS) on ease of processing and drug release were evaluated. Formulations composed of 70/30% Eudragit RL/MPT showed the fastest drug release, substituting part of Eudragit RL by RS resulted in slower drug release, all following first-order r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Repka et al (41) showed that a thermolabile drug such as hydrocortisone could be incorporated into hydroxypropylcellulose (HPC) films produced by melt extrusion (41). A US patent 7,795,237 (42) reports the use of PEG/ polypropylene glycol block copolymer in preparing solid suspensions using HME of an isobutyric acid salt, for the treatment of hepatitis C. PEO was studied for use as a drug carrier in HME using various drugs such as chlorpheniramine maleate and nifedipine (40,43,44). Among the different classes of biodegradable polymers, the thermoplastic aliphatic poly (esters) like polylactic acid (PLA), poly(glycolide) (PGA), and poly(lactide-co-glycolide) (PLGA), the copolymer of lactide and glycolide, have been used in HME.…”
Section: Materials Used In Hmementioning
confidence: 99%
See 1 more Smart Citation
“…Repka et al (41) showed that a thermolabile drug such as hydrocortisone could be incorporated into hydroxypropylcellulose (HPC) films produced by melt extrusion (41). A US patent 7,795,237 (42) reports the use of PEG/ polypropylene glycol block copolymer in preparing solid suspensions using HME of an isobutyric acid salt, for the treatment of hepatitis C. PEO was studied for use as a drug carrier in HME using various drugs such as chlorpheniramine maleate and nifedipine (40,43,44). Among the different classes of biodegradable polymers, the thermoplastic aliphatic poly (esters) like polylactic acid (PLA), poly(glycolide) (PGA), and poly(lactide-co-glycolide) (PLGA), the copolymer of lactide and glycolide, have been used in HME.…”
Section: Materials Used In Hmementioning
confidence: 99%
“…Therefore, crystalline drugs formulated using HME are mostly sustained/ controlled-release preparations. Polymer-based sustained-release matrices (using Eudragit® RL and RS as carriers) were previously processed by Quinten et al (44) via HME in combination with injection molding incorporating different metoprolol salts (tartrate, succinate, and fumarate) as the API (43). Drug release varies depending on the salt form due to the changes in the matrix hydration and permeability caused by crystal lattices.…”
Section: Apimentioning
confidence: 99%
“…This might be due to the more hydrophilic nature of RL-PO compared to RS-PO, which renders inherent water permeability, allowing a more water-soluble drug like isoniazid to diffuse better through the hydrated polymeric network. 18 Many factors may influence the rate of drug release from microparticles and one of the factors is the dissolution of polymer coat in the environment liquid, which in this case is the buffer (pH 6.8). However, since both Eudragit RL-PO and RS-PO exhibit pH independent, time-controlled release properties, pH is not a considerable factor that can affect the release of the encapsulated drug.…”
Section: In-vitro Drug Release Studymentioning
confidence: 99%
“…While sustained drug release can be achieved based on the design of the dosage form (reservoir systems vs. matrices) and/or the physicochemical properties of the polymeric materials incorporated in the formulation (diffusion controlled vs. delayed polymer dissolution), hot melt extrusion (HME) (possibly in combination with injection molding) has been evaluated to manufacture sustainedrelease matrices using various polymers: ethylcellulose (EC) [1][2][3], hydroxypropyl (methyl) cellulose (HP(M)C) [4], ethylene vinyl acetate (EVA) [5][6], polyvinyl acetate (PVA) [7], poly lactic (co-glycolic) acid (PL(G)A) [8][9], silicone [10], polycaprolactone (PCL) [11][12], polyoxazolines [13], polyanhydrides [14], methacrylate copolymers (Eudragit ® RS/RL) [15][16], and several lipid materials [17][18][19]. While sustained-release dosage forms have been successfully developed via HME using these polymers, a common drawback is that the drug load in these formulations is often low, either linked to processing issues during HME of formulations with a high drug load, or due to a significant burst release when less polymeric matrix former is incorporated in the formulation.…”
Section: Introductionmentioning
confidence: 99%
“…al. [20], for instance, described that drug load in an acrylic polymermatrix was limited to 30% when processed via HME/IM, drug release from these matrices occurred in a first order manner via a combination of swelling and diffusion. Reitz et al…”
Section: Introductionmentioning
confidence: 99%